Ledipasvir and Sofosbuvir in the Treatment of Early Hepatitis C Virus Infection in HIV-Infected Men. (21st September 2018) - Palaniswami, Paari M; El Sayed, Ahmed; Asriel, Benjamin; Carollo, Jesse R; Fierer, Daniel S; ,
Abstract: Background: Treatment of HIV-infected men during early hepatitis C virus (HCV) infection with interferon results in a higher cure rate with a shorter duration of treatment than during chronic HCV infection. We recently demonstrated that this phenomenon applied to interferon-free treatment as well, curing most participants with short-course sofosbuvir and ribavirin. Due to the significantly higher potency of the ledipasvir/sofosbuvir (LDV/SOF) combination, we hypothesized that we would be more successful in curing early HCV infections using a shorter course of LDV/SOF than that used for treating chronic HCV infections. Methods: We performed a prospective, open-label, consecutive case series study of 8 weeks of LDV/SOF in HIV-infected men with early genotype 1 HCV infection. The primary end point was aviremia at least 12 weeks after completion of treatment. Results: We treated 25 HIV-infected men with early sexually acquired HCV infection with 8 weeks of LDV/SOF, and all 25 (100%) were cured. Twelve (48%) reported sexualized drug use with methamphetamine. Conclusions: Eight weeks of LDV/SOF cured all 25 HIV-infected men with early HCV infection, including those who were actively using drugs. Based on these results, we recommend treatment of newly HCV-infected men during early infection, regardless of drug use, to both take advantage of this 8-week treatment and to decrease further HCV transmission among this group of men.